The ethical and legal protection of the vulnerable individual: Current status and prospects for the application of the guardianship institution in Italy - Ciliberti, Rosagemma (Medicina Historica, 2024)
The recent judgment of the European Court of Human Rights (ECtHR, July 6, 2023) condemning Italy for abusing the institution of legal guardianship to the detriment of Mr.  C.G. provides an opportunity for reflection on the legislation itself. In the legislator's understanding, this tool was designed to address the various and specific deficiencies (and potentialities) of individuals in vulnerable conditions in compliance with ethical principles that uphold the respect for dignity, autonomous decision-making, and equality of every human being. These areas necessitate criteria of proportionality and caution in the application of measures that interfere with very personal rights, especially those of the "vulnerable" individual.It is evident that the attention given during the construction phase of the new legal guardianship framework has yet to find equal correspondence in everyday reality raising significant implementational issues of a political, social, and ethical nature. The legal guardianship like the entire Italian judicial system, undoubtedly suffers from a chronic shortage of human and material resources, despite the concrete efforts of numerous guardianship judges and appointed support administrators. The case examined by the ECtHR prompts us to consider the necessity of ensuring greater protections for the beneficiaries, as well as respecting their right to participate in decisions concerning them. It also prompts reflection on the nature and indispensability of a relationship that finds legitimacy only in consensus, listening, and respect.